SOCIAL CONSTRUCTION OF THE HEDONIST LIFESTYLE OF FISIP STUDENTS IN THE DIGITAL ERA: A COMPARATIVE STUDY OF UMB AND KKU THAILAND - Aulia Ardha Putri; Lesti Heriyanti; Linda Safitra; Alim Bubu Swarga (Jurnal Analisa Sosiologi, 2025)
Hedonism has become a collective phenomenon among students, especially at the Faculty of Social and Political Sciences (FISIP), Universitas Muhammadiyah Bengkulu, influenced by social interaction, academic pressure, and consumerist culture through social media. This study aims to reveal the dynamics of hedonic lifestyle, the driving factors, manifestations, and their impact on students' academic and financial behaviour. A qualitative method with a phenomenological approach was used to explore the subjective meaning of the practice of hedonism. Data were collected through in-depth interviews with five informants, participatory observation, and documentation. The results showed that peer pressure, social media influence, and emotional escape are the main drivers of hedonism. Students tend to spend money on branded goods, hang out in cafes, and use financial facilities such as e-wallets and paylater. This behaviour often leads to poor financial management and negligence in studies. From the perspective of social construction theory, hedonism reflects the process of identity formation and social acceptance shaped by the campus environment and the digital world. This study concludes that hedonic tendencies are not only an individual choice but also a social reality that requires institutional attention, particularly through financial literacy education and the creation of a supportive campus environment.